Spinal Epidural Hematoma Caused by Pure Epidural Spinal Arteriovenous Malformation: Case Report and Literature Review - Elisa Garbin; Nicola Cavasin; Salima Magrini (Indian Journal of Neurosurgery, 2024)
Spontaneous spinal epidural hematoma (SEH) represents an extremely rare cause of spinal cord compression. Symptomatic pure extradural spinal AVMs (E-sAVM), in the absence of cavernous hemangiomas, are very rare and have rarely been reported. The clinical presentation of SEH caused by E-sAVM is often nonspecific and may lead to delayed diagnosis and treatment. We report the case of a 16-year-old adolescent girl who presented with paraparesis that rapidly evolved in paraplegia. Emergent magnetic resonance imaging (MRI) of the whole spine showed a posterior SEH, extending from C7 to T2, highly suspicious for the presence of an underlying AVM. The patient underwent emergent C7–T2 laminoplasty. An E-sAVM was intraoperatively found and subsequently excised. The patient was discharged with no neurological defects. E-sAVMs are extremely rare pathologies; they represent an extremely rare cause of spinal cord compression. If immediately diagnosed and treated, most patients recover with good prognosis.